The Relationship Between the Severity of Acne Vulgaris and the Quality of Life of Prima Indonesia University Medical Faculty Students - Putri Ayu Athifa Serena; Oliviti Natali; Maya Sari Mutia (GoAcademica Research & Publishing, 2023)
Acne vulgaris or acne is a chronic inflammatory disease of the pilosebaceous follicles which is characterized by the appearance of open and closed comedones, papules, pustules, nodules, seborrhea and cysts. Acne vulgaris can occur in teenagers and young adults, such as medical school students, which can affect their quality of life. The aim of this research was to determine the relationship between the severity of acne vulgaris and the quality of life of students. This type of research is analytical observational research with a cross sectional design. The population in this study were students from the Faculty of Medicine, Prima Indonesia University class 2020 – 2021 who suffered from acne vulgaris. The research sample obtained was 38 people. Sampling was purposive sampling. Data was obtained from a questionnaire filled out via the Google Form link. Data were analyzed univariately and bivariately using the Spearman Rho Rank test at a confidence level of 95% (=0.05). The results showed that the severity of acne vulgaris of students at the Faculty of Medicine, Prima Indonesia University students (71.1%) was in the mild category, the quality of life of students was in the mild disorder category (52.6%). The severity of acne vulgaris in students is significantly related to the quality of life of students at the Faculty of Medicine, Prima Indonesia University (p = 0.001 < 0.05), with the close relationship (correlation coefficient) of the two variables in the medium category (r = 0.522).